Pengaruh Persepsi Harga Dan Persepsi Kualitas Terhadap Loyalitas Pelanggan Ojek Online “XYZ” Dengan Variabel Mediasi Kepuasan Dan Kepercayaan Pelanggan - Vicki Goutama; Triyono Arief Wahyudi (STREAMING, 2025)
The objective of this research is to analyze the effect of price perception and quality perception on customer loyalty of Ojek Online “XYZ” with the customer satisfaction and customer trust as the mediating variables. This research model is developed from previous study Nafisa Choirul Mar’ati, Tri Sudarwanto, S.Pd.,M.S (2015), Lily Harjati dan Yurike Venesia (2015), Fanny Fibriyanti Salim dan Diah Dharmayanti, S.E., M.Si (2014), Ika Wahyu Wijayanti, Wahyono (2015), Woro Mardikawati, Naili Farida (2013), Muhammad Zaman Sarwar, Kashif Shafique Abbasi & Saleem Pervaiz (2012), Mai Ngoc Khuong and Ngo Quang Dai (2016), Afrina Yasmin, Sadia Tasneem, Kaniz Fatema (2015), Halizan Bin Haji Hamzah, Azli @ Meor Azli Ayub, Mohd Faiz Hilmi* (2015), I Gede Yogi Pramana, Ni Made Rastini (2016), Deddy Rakhmad Hidayat, Muhammad Riza Firdaus (2014), and also using preliminary qualitative research through in depth interview with five respondents, who were Ojek Online “XYZ” customers. There were six hypothesis that shows the relationship between variables. This research model is quantitative approach through a survey of 240 respondents using convenience sampling method. Hypothesis test results shows price perception and quality perception have a siginificant effect on customer loyalty through customer satisfaction and customer trust. The managerial implications of this research were to gain customer loyalty,  the company have to increase customer satisfaction and customer trust by making sure the certainty of  fare that  shows on the application same with the customer payment, educating customer with  promotion that better and more frequent compare to competitors, create a workshop and training to rider, and do the join promo with other company or others brand products.